On the Lower Bound of the Divisibility of Exponential Sums in Binomial Case (Communications in Mathematical Research, 2019)
In this article, we analyze the lower bound of the divisibility of familiesof exponential sums for binomials over prime field. An upper bound is given for thelower bound, and, it is related to permutation polynomials.